"As cordas de um cordel": narrativas sobre a Primeira República brasileira - Pereira, Diego Ramon Souza (2024)
This doctoral thesis analyzes the literary production of "cordel" – understood as a form of organizing worldview, information, and communication – in the context of the First Republic (1889-1930), aiming to intersect the effects of modernization and national social transformation processes initiated by the proclamation of the Republic with its reception and incorporation into the agenda of themes addressed by cordel literature. The First Republic period was marked by significant changes in political structure (end of the monarchy), economy (crisis in the primary-export model), labor (transition from slavery to wage labor), and daily life (urbanization and increasing secularization). These changes were potentially perceived, understood, and reinterpreted (positively or negatively) by popular cordel literature, widely circulated in Northeastern society at that time. Thus, this doctoral thesis starts with the question: what are the meanings of the Republic present in the narratives produced in cordel literature? To answer this, the production of a specific group of authors called the group of minor cordelists is analyzed. These authors include Silvino Pirauá de Lima, Pacífico da Silva "Cordeiro Manso", José Galdino da Silva Duda, João Melquíades Ferreira da Silva, Antonio Ferreira da Cruz, and Francisco das Chagas Batista. The hypothesis is tested that these cordelists expressed in their works the agenda of debates around social, political, economic, and cultural phenomena surrounding the emerging Republic. Simultaneously, they potentially conveyed a worldview developed according to their perspectives and values, capable of influencing the public as intellectuals. The analysis includes the labor of cordel works, their sociopolitical and cultural role in the reality of the selected period and region, reflections, and justifications regarding the selection of authors, and the verticalization of cordels produced by each author. The latter aims to map the agenda of themes over time, seeking dynamics, emphases, and types of approach, as well as to explore explanatory elements regarding the social meanings attributed to everyday facts, emotions, religion, social roles, politics, the growing hegemony of the urban-industrial world represented by the southeast, and the drastic ongoing world events. The qualitative approach of the thesis relies on Discourse Theory to analyze 23 complete narratives from a cataloged universe of 41 cordels, created by the six cordelists of the group of minor cordelists. The thesis demonstrates that cordels are important materials for analyzing social thought since cordelists, acting as intellectuals, echo critical views of modernization and republicanism, as well as conservative tones through narratives reinforcing religious values (Catholicism). The Republic is criticized, especially regarding tax collection and the increase in inequalities. The Northeastern people are valued while stories of local disputes and national/international events are narrated. There is also a duality between modernization and tradition (curiosity and fear). Finally, by discussing transformations in the context of the First Republic, the narratives shed light on changes in the social fabric of the Northeast.